An integrated bioinformatics analysis to dissect kinase dependency in triple negative breast cancer. (December 2015) - Ryall, Karen; Kim, Jihye; Klauck, Peter; Shin, Jimin; Yoo, Minjae; Ionkina, Anastasia; Pitts, Todd; Tentler, John; Diamond, Jennifer; Eckhardt, S; Heasley, Lynn; Kang, Jaewoo; et al.
Abstract Background Triple-Negative Breast Cancer (TNBC) is an aggressive disease with a poor prognosis. Clinically, TNBC patients have limited treatment options besides chemotherapy. The goal of this study was to determine the kinase dependency in TNBC cell lines and to predict compounds that could inhibit these kinases using integrative bioinformatics analysis. Results We integrated publicly available gene expression data, high-throughput pharmacological profiling data, and quantitativein vitro kinase binding data to determine the kinase dependency in 12 TNBC cell lines. We employed Kinase Addiction Ranker (KAR), a novel bioinformatics approach, which integrated these data sources to dissect kinase dependency in TNBC cell lines. We then used the kinase dependency predicted by KAR for each TNBC cell line to query K-Map for compounds targeting these kinases. Wevalidated our predictions using published and new experimental data. Conclusions In summary, we implemented an integrative bioinformatics analysis that determines kinase dependency in TNBC. Our analysis revealed candidate kinases as potential targets in TNBC for further pharmacological and biological studies.